Simulated steerability of a segmented rubber tracked vehicle during turning on sepang peat terrain in Malaysia - Rahman, Mohammed Ataur; Azmi , Yahya (Inderscience Enterprises Ltd., 2005)
A simulation study on the steerability of a segmented rubber tracked vehicle on lowbearing- capacity peat terrain is performed by considering the position of the vehicle's turning pole. A set of mathematical equations in the analytical model is used to predict all the important operating parameters of the vehicle during turning to establish the vehicle's steerability. Seven road wheels are used on each side of the track in order to avoid the track deflection between two consecutive road wheels. A road wheel diameter of 0.22 m and road wheel spacing of 0.225 m are employed to keep the track on the terrain as a rigid footing. The simulation of vehicle steerability in this study is focused on considering the vehicle's speed of 10 km/h. The turning pole coincides with the same level of the amount of eccentricity of nominal ground pressure and the resultant turning moment resistance.